Sharing the Patient Experience: A "Talk Story" Intervention for Heart Failure Management in Native Hawaiians. (June 2020) - Sentell, Tetine; Kennedy, Fiona; Seto, Todd; Vawer, May; Chiriboga, Germán; Valdez, Coraleen; Garrett, Lisa M; Paloma, Diane; Taira, Deborah
Background: Native Hawaiians (NHs) suffer disproportionately from cardiovascular disease morbidity and mortality. Objective: To test a narrative intervention of patient stories to support heart disease self-management in NHs. Method: Six NH storyteller videos were developed with community feedback following established methods. The NH participants with heart failure (N = 35) were recruited from a major medical center in Hawai'i. Participants completed demographic questionnaires, watched videos via iPad, and described experiences. Follow-up was 4 weeks later. Results: Mean participant age was 57.0 years (standard deviation [SD]:13.0) and 31% (11) were female. On a scale of 1 (worst) to 4 (best), respondents rated the videos 3.7 (SD: 0.5) in relevance for helping them manage their heart disease and 3.6 (SD: 0.5) in their experience using these videos. When asked what they liked best, the most common response was that they are "like me" (from 14 respondents, ranging from a 43-year-old woman to an 84-year-old man). Of those completing follow-up (n = 15), 87% said videos helped them. Conclusion: Our narrative "talk story" intervention showed promise as a culturally relevant method to share patient experiences and reduce health disparities.